Analysis of Piano Performance Characteristics by Deep Learning and Artificial Intelligence and Its Application in Piano Teaching - Li, Weiyan (Frontiers in Psychology, 2022)
Deep learning (DL) and artificial intelligence are jointly applied to the concrete piano teaching of children to comprehensively promote modern piano teaching and improve the overall teaching quality. Firstly, the teaching environment and the functions of intelligent piano are expounded. Then, a piano note onset detection method is proposed based on convolution neural network (CNN). The network can analyze the time-frequency of the input piano music signal by transforming the original time-domain waveform the piano music signal into the frequency distribution varying with time. Besides, it can detect the note onset at a stable state after 8×104 iterations. Moreover, an intelligent piano teaching method is designed to teach Jingle Bells for 40 preschool children aged 4-6 years. Finally, a questionnaire survey is performed to investigate the teaching situation, including the learning interest and learning effect of children and learning feedback from parents. The results show that 80% of children like smart music scores, 82% of children like intelligent piano lessons with games, and 84% of children can learn actively in intelligent piano class. Besides, 85% of parents believe that their children are more interested in learning piano. In general, the intelligent piano teaching method effectively combines DL with AI to realize the overall optimization of piano performance. It is widely favored by preschool children and their parents, and plays an important role in improving preschool children's interest in piano learning.